Edukasi Kerajinan dari Botol Plastik sebagai Media Tanam guna Menambah Penghasilan Rumah Tangga Sekitar Desa Cicalengka Kabupaten Tangerang - Ariyanti, Eti; Wardani, Endang Susilo; Irawati, Laila (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The increasing need to improve household income in rural areas has encouraged innovative approaches to community empowerment. This study focuses on educating the residents of Desa Cicalengka, Banten, on crafting plant media from recycled plastic bottles, aiming to promote environmental awareness and provide alternative income sources. The purpose of this community service activity was to enhance the economic capacity of local households by equipping them with practical skills in upcycling plastic waste into useful planting containers. The activity was conducted at the Desa Cicalengka Office, Pagedangan, Tangerang Regency, Banten, on September 28-29, 2024. The implementation involved 12 lecturers from Universitas Pamulang and 31 community members from Desa Cicalengka. The methods included material presentation, hands-on practice, group discussions, and question-and-answer sessions to ensure comprehensive understanding and skill acquisition. Results indicated that participants successfully created functional planting media from plastic bottles and expressed increased awareness of waste management and income diversification. This initiative not only promoted sustainable environmental practices but also empowered the community by providing them with a simple, replicable technique to generate additional household income. The positive reception suggests the potential for scaling and integration into wider community development programs.